Hubungan Paritas Dengan Kejadian Bayi Berat Lahir Rendah - Exna Putri, Meilina Angita; Toyibah, Afnani; Setyarini, Arika Indah (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
Low Birth Weight Babies (LBW) are still very important in public health, with variables defined by WHO as weighing less than 2500 grams at birth. Birth with LBW is still a major factor in increasing mortality, morbidity and disability in neonates, infants and children, so that it can have a long-term impact on future life. This study aims to determine whether there is a relationship between parity and the incidence of low birth weight babies. This study uses a literature review design. Search journal articles using the PICO format and analysis was carried out. The search was carried out on several databases, namely Google Scholar, PubMed and DOAJ using keywords that had been determined by the researchers (Parity and Low Birth Weight Babies, Relationship and Parity Low Birth Weight Babies, Parity and LBW, or Parity and Low Birth Weight Babies, or The Relationship between Parity and Low Birth Weight Babies). Of the 10 journals from 2016 to 2020, which have been analyzed, there are 8 journals which state that there is a relationship between parity and the incidence of LBW. There is a relationship between parity and the incidence of low birth weight babies. The need for increased monitoring and provision of IEC to mothers with risk factors, so that they can overcome the incidence of LBW in early pregnancy